2009
DOI: 10.1183/09031936.00050809
|View full text |Cite
|
Sign up to set email alerts
|

Rapid on-site evaluation of transbronchial aspirates: randomised comparison of two methods

Abstract: The value of different staining methods for rapid analysis of transbronchial needle aspirates during bronchoscopy has not been explored.In the present study, we compared a Papanicolaou-based rapid stain, prepared by a technologist and read by a cytopathologist, and a Wright-Giemsa-based rapid stain, prepared and read by a cytopathologist alone. Gold standard was the final laboratory report issued on each aspirate.We harvested 827 aspirates from 218 target sites in 126 consecutive patients. At least one positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…The touch preparation slides are then either air‐dried and stained with Diff‐Quik stain per standard protocols or ethanol‐fixed and stained with rapid Pap stain per standard protocols. From our study, there was a higher proportion of rapid Pap‐stained slides that were interpreted as non‐diagnostic due to hypocellularity as compared to Diff‐Quik stained slides, possibly related to the differences in stain preparation, although these results are in contrast with other studies in the literature in which rapid Pap stain was found to have superior yield and accuracy . At our facility, more cytopathologists prefer to utilize the rapid Pap stain.…”
Section: Discussioncontrasting
confidence: 72%
“…The touch preparation slides are then either air‐dried and stained with Diff‐Quik stain per standard protocols or ethanol‐fixed and stained with rapid Pap stain per standard protocols. From our study, there was a higher proportion of rapid Pap‐stained slides that were interpreted as non‐diagnostic due to hypocellularity as compared to Diff‐Quik stained slides, possibly related to the differences in stain preparation, although these results are in contrast with other studies in the literature in which rapid Pap stain was found to have superior yield and accuracy . At our facility, more cytopathologists prefer to utilize the rapid Pap stain.…”
Section: Discussioncontrasting
confidence: 72%
“…Second, the pulmonologist diagnosed specimens with DiffQuikÂź staining, whereas cytopathologists diagnosed specimens with Papanicolaou staining. Because a Papanicolaou‐based stain has superior yield and accuracy than a Wright‐Giemsa‐based stain for ROSE of transbronchial needle aspirates, there is a possibility that sensitivity and specificity differ between stains. Each specimen is unique and therefore different specimens were analysed by the pulmonologist and cytopathologists.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been validated for epithelial carcinomas and tuberculosis, where ROSE has been shown to have a high sensitivity for identifying diagnostic material and suggesting a provisional diagnosis [10,11,12,26,27]. Although cytology may be diagnostic in other types of pathology, further investigations are often required and the value of ROSE is therefore less well defined [28].…”
Section: Discussionmentioning
confidence: 99%